KAJIAN TENTANG RENCANA REDENOMINASI RUPIAH DALAM SISTEM KEUANGAN JANGKA PANJANG DI INDONESIA - Putri, Anisa (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2011)
Too much small change is not efisien because it makes the proless of payment and cash transaction more difficult, reducing the small change can simplify the system of accountancy and payment. Redenomination simplifies the money without reducing the value of it. The plan of redenomination must be done carefully. The pyshicological effect for society and investor will depend on how Indonesian Bank socializes it. The readiness of society is needed because economical fluctuation can happen and the society will panic. It is dangerous because the society do not understand and it should be prevented from misunderstanding. The strong economics and politics stabilizing will be easy in redenomination process. If bussinessmen are sure that economics work well. However, if businessmen think that economics gets worse, the redenomination will cause the number if inflation to increase. The success of redenomination can be done only in low stabilizing inflation and inflation of expectancy.